NAS and auditor independence: evidence from Malaysian listed construction companies / Wan Zurina Nik Abdul Majid … [et al.] - Nik Abdul Majid, Wan Zurina; Azizi, Muhammad Amiruddin; Marzuki, Marziana Madah; Muhamad Hanafi, Nurfazilahaini; Hassan, Othman Zailani (2021)
Construction industry in Malaysia has been associated with various scandals of corruption and fraud cases over the years, which raised the question of the functionality and independence of the external auditor. Whether the provision of non-audit services (NAS) has affected auditor independence or not in construction companies is still unexplored. Therefore, this study tends to examine the relationship between NAS (NAS) and auditor independence of construction companies in Malaysia. The study also includes the control variables, which are grouped into financial, corporate governance and institutional. The study employs descriptive analysis, univariate tests and multivariate regression to investigate the potential effect of NAS on auditor independence. The data for NAS and other control variables were hand collected from annual reports downloaded from Bursa Malaysia’s website. Based on 147 firm-year observations of construction companies for the period 2017-2019, the study found that the joint produce of audit and NAS did not compromise auditor independence. This empirical result failed to prove the economic bond created between auditors and clients, which restricted the auditors from performing their duty objectively. The finding supported the argument of knowledge spillover in which the auditor gained experience and yielded audit efficiency while doing the audit. These results contributed to Malaysia’s policy deliberation to account for the effects of NAS on auditor independence using the direct method of audit opinion. This study contributes to theoretical perspectives on knowledge spillover, which is very limited in Malaysia.